The Development of a Multimedia-Based Student Activity Sheet on Physical Fitness Materials for Class Ten - Bakhtiar Rifai; Nanik Indahwati; Gigih Siantoro (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to develop student worksheets (LKPD) for physical fitness material in grade tenth where the aspects developed include (1) developing student activity sheet models (2) content development. Using research development methods from Borg and Gall with quantitative and qualitative approaches. Qualitative data were analyzed descriptively qualitatively. 75 students as a small-scale test sample and 205 students as a large-scale test sample. The research was conducted at SMAN 3 Pasuruan. The feasibility of developing multimedia-based worksheets on tenth-grade physical fitness materials is based on the assessment of (a) Education Experts, getting an overall average score of 4.2 with a decent category. (b) Media experts got an overall average score of 3.8 with a very decent category, (c) the first trial / small scale got an overall average score of 4. with a decent category or LKPD model and content developed according to students, (d) The second trial/large scale got an overall score average of 3.9 with a decent category or model and LKPD content developed according to students. Based on these results, the multimedia-based LKPD on competencies 3.4 and 4.4 the concept of exercise and measuring the components of physical fitness for a tenth grade in each aspect developed is feasible to use and according to students so that it is feasible to produce for learning.